Prefrontal Cortex - Starcevic, Ana; Filipovic, Branislav (IntechOpen, 2018)
The prefrontal cortex reaches its greatest development in the human brain, making up nearly one third of the neocortex. Due to its remarkable evolution, the prefrontal cortex plays an important role in higher integrative functions such as information processing, thinking, understanding, attention, behavior, motivation, emotions, working memory, and analysis. This book brings together theoretical and technical research advances on the prefrontal cortex, from the basic explanations of the neuronal architecture of the prefrontal cortex and its anatomy, presenting it as a morphological substrate for many psychological conditions, through normal and altered connectivity and its manifestation in different behavior and identification of organizational levels inside the prefrontal cortex through different neuroimaging methods. It also provides an interdisciplinary view of the prefrontal cortex and its issues and discovers the main role of this part of brain in psychosocial, economic, and cultural adaptation.